Seismic stratigraphic analysis of the Middle-Upper Jurassic Krossfjord and Fensfjord formations, Troll oil and gas field, northern North Sea - Holgate,NE; Jackson,CA-L; Hampson,GJ; Dreyer,T (Marine and Petroleum Geology, 2015)
The “syn-rift” Middle-to-Late Jurassic Krossfjord and Fensfjord formations, Troll Field, northern North Sea contain a complex distribution of wave- and tide-dominated deltaic, shoreline and shelf depositional environments of varying reservoir potential. Uncertainty exists in depositional models used to explain the spatial and temporal distribution of these depositional environments and the absence of coeval coastal plain deposits. To date, the proposed influence of growing rift-related structures on stratigraphic architectures and sedimentation patterns in the units has been poorly defined. In this study, 3D seismic data are integrated with core, biostratigraphic and wireline-log data to produce a consistent geological interpretation for the formations. Seismic analysis has identified nine parasequences (‘series’) containing NNE-SSW-striking, delta-scale clinoforms that prograded westwards over much of the field. Quantitative analysis highlights an increase in height and dip of clinoforms from proximal to distal locations, coincident with an increase in grain size. Clinoform geometry is sigmoidal, with well-developed topsets that, based on core data, lack subaerial deposits. These geometrical and sedimentological characteristics suggest that a subaqueous delta depositional system deposited the Krossfjord and Fensfjord formations in the Troll Field. In the northeast of the field, clinoforms exhibit highly variable strike and oblique cross-sectional geometries, which suggest that sediment was supplied from here, and then redistributed through southward-directed wave and longshore current activity. Rift-related faulting is recognised to have occurred in thewestern part of the Troll Field only during deposition of the youngest Fensfjord Formation ‘series’, thus challenging the notion that these units are ‘syn-rift’. Seismically imaged clinoforms in the under-explored area south of the Troll Field prograded southward, and a